Properties of Solar Wind Structures at Mercury's Orbit. Issue 9 (18th September 2020) - Diego, P.; Piersanti, M.; Laurenza, M.; Villante, U.
Abstract: Mercury's environment is characterized by a high variability and strength of the solar forcing. Its magnetosphere is completely reconfigured even for small changes in the interplanetary magnetic field and the solar wind (SW) dynamic pressure. Different configurations are due to occurrence of different structures in the SW. Among them, high speed streams from coronal holes, magnetic clouds, and noncompressive density enhancement have been analyzed to better characterize the Hermean conditions, which might be expected during the ongoing BepiColombo mission. Helios 1 and 2 mission data collected between 0.29 and 0.47 AU have been used to perform a statistical analysis of these SW structures. The numerical results reported in the paper, as well as the probability densities displayed in the maps, give more precise indications when associated to a rigorous SW structures selection. The occurrence rate along solar cycle together with the average features of each class of SW structures are useful information for Space Weather topics. Results from the same analysis performed at 1 AU have been used to further verification of the radial behavior of the SW parameters. Key Points: Properties of the different solar wind structures between 0.29 and 0.47 AU are compared Alfvénic and sonic Mach number typical values between 0.3 and 1 AU for different solar wind structures are identified Highest solar wind dynamic pressures at Mercury orbit, 15 to 30 nPa, occur during noncompressive density enhancements